Boron nitride and oxide supported on dendritic fibrous nanosilica for catalytic oxidative dehydrogenation of propane - Belgamwar, Rajesh; Rankin, Andrew G. M.; Maity, Ayan; Mishra, Amit Kumar; Gomez, Jennifer S.; Trebosc, Julien; Vinod, Chathakudath P.; Lafon, Olivier; Polshettiwar, Vivek (ACS Sustainable Chemistry & Engineering, 2020)
In this work, we were able to significantly increase the activity of boron nitride (BN) catalysts used for the oxidative dehydrogenation (ODH) of propane by designing and synthesizing BN supported on dendritic fibrous nanosilica (DFNS). DFNS/BN showed a markedly increased catalytic efficiency, accompanied by exceptional stability and selectivity. Textural characterization, together with solid-state nuclear magnetic resonance (NMR) and X-ray photoelectron spectroscopic analyses, indicates the presence of a combination of unique fibrous morphology of DFNS and various boron sites connected to silica to be the reason for this increase in the catalytic performance. Notably, DFNS/B2O3 also showed catalytic activity, although with more moderate selectivity compared to that of DFNS/BN. Solid-state NMR spectra indicate that the higher selectivity of DFNS/BN might stem from a larger amount of hydrogen-bonded hydroxyl groups attached to B atoms. This study indicates that both boron nitride and oxide are active catalysts and by using high surface area support (DFNS), conversion from propane to propene as well as productivity of olefins was significantly increased.
Keywords: Electron microscopy; heterogeneous catalysis; Nanostructures; NMR spectroscopy; propane dehydrogenation; X-ray diffraction; X-ray photoelectron spectroscopy

Lithium silicate nanosheets with excellent capture capacity and kinetics with unprecedented stability for high-temperature CO2 capture - Belgamwar, Rajesh; Maity, Ayan; Das, Tisita; Chakraborty, Sudip; Vinod, Chathakudath P.; Polshettiwar, Vivek (Chemical Science, 2021)
An excessive amount of CO2 is the leading cause of climate change, and hence, its reduction in the Earth's atmosphere is critical to stop further degradation of the environment. Although a large body of work has been carried out for post-combustion low-temperature CO2 capture, there are very few high temperature pre-combustion CO2 capture processes. Lithium silicate (Li4SiO4), one of the best known high-temperature CO2 capture sorbents, has two main challenges, moderate capture kinetics and poor sorbent stability. In this work, we have designed and synthesized lithium silicate nanosheets (LSNs), which showed high CO2 capture capacity (35.3 wt% CO2 capture using 60% CO2 feed gas, close to the theoretical value) with ultra-fast kinetics and enhanced stability at 650 degrees C. Due to the nanosheet morphology of the LSNs, they provided a good external surface for CO2 adsorption at every Li-site, yielding excellent CO2 capture capacity. The nanosheet morphology of the LSNs allowed efficient CO2 diffusion to ensure reaction with the entire sheet as well as providing extremely fast CO2 capture kinetics (0.22 g g(-1) min(-1)). Conventional lithium silicates are known to rapidly lose their capture capacity and kinetics within the first few cycles due to thick carbonate shell formation and also due to the sintering of sorbent particles; however, the LSNs were stable for at least 200 cycles without any loss in their capture capacity or kinetics. The LSNs neither formed a carbonate shell nor underwent sintering, allowing efficient adsorption-desorption cycling. We also proposed a new mechanism, a mixed-phase model, to explain the unique CO2 capture behavior of the LSNs, using detailed (i) kinetics experiments for both adsorption and desorption steps, (ii) in situ diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy measurements, (iii) depth-profiling X-ray photoelectron spectroscopy (XPS) of the sorbent after CO2 capture and (iv) theoretical investigation through systematic electronic structure calculations within the framework of density functional theory (DFT) formalism.